Economic evaluation on fish production and demand in Tripura - strategic options - DEBNATH, BISWAJIT; BIRADAR, R S; KRISHNAN, M; PANDEY, S K; DEBNATH, C; SRIVASTAVA, S K; DAS, S C S (The Indian Journal of Animal Sciences, 2015)
Tripura, witnessed an impressive growth in fish production during the past decade, because here fish culture is recognized as a vital activity for economic development. The state is presently undergoing a transitional phase and developing several plans to achieve self-sufficiency in fish production. The present study aims to workout strategic options that harmonize production and consumption. Stochastic frontier production function and technical efficiency of fish production estimates yielded positive coefficients for majority of factors of production. It showed significantly higher mean technical efficiency for adopted villages than that for non-adopted villages. At consumption front, demand estimation using multiple budgeting framework of household showed significant and positive income elasticities of demand for local carps, local non-carps, inter-state non-carps and small weed fish. But income elasticity for inter-state carps was less and insignificant among all selected choice fish groups (CFGs). Demand for the fish under the baseline scenario (base year 2004) is likely to grow at an annual rate of 3.38% for the State. The demand for fish by 2015 was projected as 80,153 mt of which nearly 50% (40,624 mt) is constituted by local carps. The study suggested prioritizing technological and management options after synchronizing present policy of the fisheries development, institutional environment, support services and profile of different stakeholders of the state.